Preparation and Performance of Urea-Formaldehyde Resin Modified with Phenolized Fulvic Acid and Isocyanate - Zhang, Xianglin; Xu, Jun; Dai, Rongjia; Chen, Houwei (Asian Journal of Chemistry, 2014)
Urea-formaldehyde (UF) resins were prepared by using phenolized fulvic acid (PFA) and 4,4'-diphenylmethane diisocyanate (MDI) as modifiers through orthogonal experiment. The influence of the PFA/UF ratio (mass ratio) on free formaldehyde and that of the MDI/UF ratio on bonding strength were investigated. The results showed that the content of free formaldehyde decreased with an increasing PFA/UF ratio and the bonding strength increased with an increasing MDI/UF ratio. When the mass ratio of PFA:MDI:UF was 0.006:0.035:1, the free formaldehyde content was dropped to 0.0924 %, the bonding strength could be achieved at 1.08 MPa and the thermal stability was also improved accordingly.